Marketing Strategy for Home-Produced Banana Chips in Sigara-Gara Village, Patumbak District North Sumatra - Effendi, Nazwa Aliya; Hanjani, Eni; Altito, Muhammad Rifky Seno; Sitompul, Hamela Sari (Journal of Agriculture, 2024)
This study analyzes the marketing strategy of banana chip products at the Keripik Ayu Ketaren MSME in North Sumatra. Although Indonesia is the largest banana producer in the world, the utilization of banana harvests is still relatively low. Banana chips, on the other hand, have significant market potential, especially as a healthy snack option. This study uses a SWOT analysis to identify MSMEs' strengths, weaknesses, opportunities, and threats. The results of the analysis show several strengths, such as good product durability and affordable prices, which can be utilized to expand the market. However, challenges such as limited capital and distribution networks must be addressed to support growth. Existing opportunities, including the increasing demand for healthy snacks and the potential of digital platforms, can help expand market reach. On the other hand, threats from larger competitors and lack of product innovation are risks that must be faced to overcome these challenges; the recommended strategies include improving packaging quality, flavor innovation to attract new consumers, and utilizing digital and e-commerce platforms to reach a wider audience. This study aims to provide valuable insights for MSME actors in developing effective marketing strategies, increasing the competitiveness of banana chip products, and supporting business sustainability in an increasingly competitive market.